Les enjeux du végétal dans une ville du « Sud » - Mustapha El Hannani; Aude Nuscia Taïbi; Naïma Brabra; Sigrid Giffon (Projets de Paysage)
Marrakesh was developed based on the classic model of the garden-city imbedded in an oasis. In the iconography and descriptions of writers and travellers, Marrakesh is indissociable from its palm groves and plants which confer a strong identity to a landscape the city has promoted for tourism. This image has increasingly become disconnected from reality, the garden-city and oasis image is fading away in the face of the extension and densification of the city. The palm groves and rows of trees have been retreating with encroaching urbanisation, golf courses, tourist complexes and villas, ever since the colonial period and increasingly in recent decades. The composition of this plant heritage is a reflection of various cultural influences which have shaped the current identity of the city. The palette of plant species reveals a qualitative change in landscapes correlated to changes in the tastes and choices of a social class and a population which questions this identity, historically based on a balance between plant and mineral elements. Gentrification has led to food production being abandoned to the benefit of recreational and aesthetic landscape functions.